Development of Fiqh Teaching Materials Based on Internalization of Social Values in class XI SMA IT Al-Mawaddah Warrahmah Kolaka - Hasania, Sitti; Nurhayati, Nurhayati; Hartono, Hartono (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to develop and test a Fiqh teaching material based on the internalization of social values for 11th-grade students at SMA IT Al-Mawaddah Warrahmah Kolaka. The teaching material was validated by experts using four evaluation aspects: content feasibility, language feasibility, presentation feasibility, and graphic feasibility. The validation results show that the teaching material is categorized as highly valid, with an average score of 3.50. Furthermore, the practicality test was conducted by observing the implementation of the teaching process by four observers who assessed aspects such as learning syntax, interaction, classroom management, and the use of teaching aids. The practicality test results indicate that the teaching material was fully implemented, with an average score of 1.75. The effectiveness of the teaching material was measured by comparing pre-test and post-test results using the gain index. The results show that the average gain score of students is 0.80, categorized as high. The findings of this study indicate that the Fiqh teaching material based on the internalization of social values is effective in improving students' learning outcomes, and is very practical and valid for use in teaching. Therefore, this teaching material can be used as a model for developing learning resources in Fiqh education and is expected to help students understand the social concepts in Islamic law.